The Development of Sekrebel Application Based on Folklore For High School Students - Ayu Chandra Dewi; Sumarwati; Kenfitria Diah Wijayanti (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2025)
The introduction of Javanese script to the younger generation, especially high school students, has become a challenge in today's digital era. Lack of interest and less interactive learning methods have led to low literacy in Javanese script. Therefore, this study aims to develop the "Sekrebel" application based on folklore as an interactive learning medium that appeals to high school students. This application combines educational and entertainment elements through folklore presented in Javanese script and Latin transliteration. The study results show that using this application significantly improves students' understanding and skills in reading and writing Javanese script.